Mapping the evolution of fertility support policies in China: A content and instrumental analysis - Ying Yue; Xiaojun Yang; Jie Ma (PLoS ONE, 2025)
Fertility support policies encompass measures providing economic, time, and childcare assistance to families with children. In China, these policies have continuously evolved in response to demographic shifts and changing socioeconomic environments. This study analyzes 226 policy texts across four stages using content analysis to examine two important dimensions—policy content and policy instruments. The results demonstrate that services and other forms of support outnumber time and financial provisions, reflecting a gradual diversification of policy content. Mandatory instruments are used more frequently than hybrid and voluntary ones, though the overall application of instruments is balanced. Different types of policy content employ distinct policy instruments. Moreover, the evolution of these policies reflects a process of adaptation to changing social contexts, the evolving role of women, and improved efficacy. However, current policies still face challenges including insufficient use of voluntary and hybrid instruments and inadequate attention to gender equality. To enhance fertility support, we recommend diversifying the use of instruments away from mandatory ones towards hybrid and voluntary options, ensuring comprehensive and inclusive policy content, and improving coordination across policy tools.